2000
DOI: 10.1111/j.1572-0241.2000.03294.x
|View full text |Cite
|
Sign up to set email alerts
|

Leptin has no role in determining severity of steatosis and fibrosis in patients with chronic hepatitis C

Abstract: These findings suggest that the degree of steatosis in patients with CHC does not seem to depend on serum leptin levels or on viral factors, at least as far as HCV viremia and genotype and HGV infection are concerned. The severity of fibrosis does not seem to be influenced by leptin levels, whereas HCV viral load does seem to play some role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
39
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 32 publications
4
39
0
1
Order By: Relevance
“…33,34 In earlier studies, leptin levels in HCV-infected subjects were similar to those in healthy volunteers matched for age, BMI and gender. 28,35 Serum leptin was found to be associated with IR, 15,37 steatosis 36 and fibrosis 29,30 in some but not all reports. 13,28,30,35,38 With regard to adiponectin, a recent report suggested that adiponectin levels do not differ significantly between healthy subjects and patients with HCV infection after adjusting for age, BMI and gender.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…33,34 In earlier studies, leptin levels in HCV-infected subjects were similar to those in healthy volunteers matched for age, BMI and gender. 28,35 Serum leptin was found to be associated with IR, 15,37 steatosis 36 and fibrosis 29,30 in some but not all reports. 13,28,30,35,38 With regard to adiponectin, a recent report suggested that adiponectin levels do not differ significantly between healthy subjects and patients with HCV infection after adjusting for age, BMI and gender.…”
Section: Discussionmentioning
confidence: 99%
“…28,35 Serum leptin was found to be associated with IR, 15,37 steatosis 36 and fibrosis 29,30 in some but not all reports. 13,28,30,35,38 With regard to adiponectin, a recent report suggested that adiponectin levels do not differ significantly between healthy subjects and patients with HCV infection after adjusting for age, BMI and gender. 39 Furthermore, adiponectin levels were not associated with steatosis, portal/periportal inflammation grade, or fibrosis stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering a close link between adipocytokines and IR, 8 it is thus reasonable to speculate that adipocytokines could also contribute, at least in part, to fibrosis progression. Although the association between leptin and steatosis in CHC remains controversial, 3,9 prior studies showed that hypoadiponectinemia was associated with steatosis in CHC. 2 Because the progression from steatosis to fibrosis may take time, 10 the negative association between adipocytokines and the extent of histological injury observed in the present study may be attributed to the time effect.…”
mentioning
confidence: 99%